Fiber Optic Introduction Workshop for Students SMK Triyadikayasa Aek Songsongan - Ruri Ashari Dalimunthe; Riki Andri Yusda; Rendy Fahrezi Ramadhan; Hariansyah Jufri (STMIK Royal, 2022)
Abstract: The community service activity entitled